Legal Analysis of the Protection of the Rights and Obligations of Female Workers in the Manufacturing Industry from the Perspective of Labor Law Based on Law No. 6 of 2023 Concerning Job Creation - Dwi Atmoko; Sugeng Sugeng (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Currently, the development of the manufacturing industry in Indonesia is experiencing quite rapid growth. Investors are entering Indonesia, many of them establishing companies that certainly require a lot of workers, including female workers. As is known, the emergence of the Employment Law contained in Law No. 6 of 2023 concerning Job Creation provides a